The role of 3′UTR-protein complexes in the regulation of protein multifunctionality and subcellular localization - Ribeiro, Diogo M; Prod’homme, Alexis; Teixeira, Adrien; Zanzoni, Andreas; Brun, Christine (Nucleic acids research, 2020)
Abstract Multifunctional proteins often perform their different functions when localized in different subcellular compartments. However, the mechanisms leading to their localization are largely unknown. Recently, 3′UTRs were found to regulate the cellular localization of newly synthesized proteins through the formation of 3′UTR-protein complexes. Here, we investigate the formation of 3′UTR-protein complexes involving multifunctional proteins by exploiting large-scale protein-protein and protein-RNA interaction networks. Focusing on 238 human ‘extreme multifunctional’ (EMF) proteins, we predicted 1411 3′UTR-protein complexes involving 54% of those proteins and evaluated their role in regulating protein cellular localization and multifunctionality. We find that EMF proteins lacking localization addressing signals, yet present at both the nucleus and cell surface, often form 3′UTR-protein complexes, and that the formation of these complexes could provide EMF proteins with the diversity of interaction partners necessary to their multifunctionality. Our findings are reinforced by archetypal moonlighting proteins predicted to form 3′UTR-protein complexes. Finally, the formation of 3′UTR-protein complexes that involves up to 17% of the proteins in the human protein-protein interaction network, may be a common and yet underestimated protein trafficking mechanism, particularly suited to regulate the localization of multifunctional proteins.